Pengaruh Literasi Ekonomi Terhadap Perilaku Konsumtif Mahasiswa Jurusan Pendidikan Ekonomi Universitas Siliwangi - Ai Nur Solihat; Syamsudin Arnasik (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
This study aims to determine the description of the influence of economic literacy on student consumptive behavior Department of Economic Education Siliwangi University. The method used in this research is a descriptive method. The population in this study are students of the Department of Economic Education Siliwangi University. The sampling technique used in this study is simple random sampling with 251 respondents. Data collection techniques in the form of tests, questionnaires, and documentation. Data analysis technique used in this research is a simple linear regression, where the independent variable (X) is economic literacy and the dependent variable (Y) is consumptive behavior. The results show that economic literacy has a significant influence on student consumptive behavior. This means that if there is an increase in economic literacy, the more rational student consumptive behavior.